Arqueologia da Região Meridional da Península de Setúbal : breve síntese baseada nos principais testemunhos arqueológicos - Cardoso, João Luís (2015)
Brief synthesis of the archaeological remains found in the meridional area of the Setúbal Península. The author introduces information from recent discoveries and presents a new approach to facts already known. In this summary, archaeological remains from the Paleolithic to the Early Medieval Age are analysed.